Molecular effects of encapsulation of glucose oxidase dimer by graphene1. Issue 18 (5th March 2015) - Ghoshdastider, Umesh; Wu, Rongliang; Trzaskowski, Bartosz; Mlynarczyk, Krzysztof; Miszta, Przemyslaw; Gurusaran, Manickam; Viswanathan, Sowmya; Renugopalakrishnan, Venkatesan; Filipek, Slawomir
<x xml:space="preserve">Abstract</x> A box-like shape of graphene leads to different types of "sandwich" or "burrito" encapsulation of the enzyme. To preserve the critical interactions in the enzyme active site a proper balance of forces between protein and graphene is required.